149k views
4 votes
Question in the below, i know it’s NOT A

Question in the below, i know it’s NOT A-example-1

2 Answers

5 votes

Answer:

4.
x^{((7)/(4))} = \sqrt[7]{x^4}

Explanation:

Here, consider the each expression and simplify it:

1.
x^{(1)/(8) }* x^{(1)/(8)

Now, if the BASE IS SAME when multiplied, THE POWERS ARE ADDED.


x^{(1)/(8) }* x^{(1)/(8)} = x^{((1)/(8) + (1)/(8))}\\= x^{((1)/(4))} =\sqrt[4]{x} \\\implies x^{(1)/(8) }* x^{(1)/(8)} = \sqrt[4]{x}

Hence, given statement if TRUE.

2.
\frac{x^{(2)/(5) }}{x^{(1)/(5) }}

Now, if the BASE IS SAME when divided, THE POWERS ARE SUBTRACTED.


\frac{x^{(2)/(5) }}{x^{(1)/(5) }} = x^{((2)/(5) ) -((1)/(5) )} = x^ {((1)/(5))} = \sqrt[5]{x} \\\implies \frac{x^{(2)/(5) }}{x^{(1)/(5) }} = \sqrt[5]{x}

Hence, given statement if TRUE.

3.
x^{((7)/(9))

Now,a s we know :
x^{((1)/(a)) } = \sqrt[a]{x}

So, solving given expression:
x^{((7)/(9))} = \sqrt[9]{x^7}

Hence, given statement if TRUE.

4.
x^{((7)/(4))

Now,a s we know :
x^{((1)/(a)) } = \sqrt[a]{x}

So, solving given expression:
x^{((7)/(4))} = \sqrt[4]{x^7} \\eq \sqrt[7]{x^4}

Hence, given statement if FALSE.

User John Gathogo
by
5.4k points
2 votes

Answer:

Option D) is correct

That is the rational exponent expression is not simplified correctly is


x^{(7)/(4)=\sqrt[7]{x^4}

Explanation:

Given rational exponent expression is
x^{(7)/(4)=\sqrt[7]{x^4}

To prove that LHS=RHS

First taking LHS


x^{(7)/(4)


=(x^7)^{(1)/(4)}


=\sqrt[4]{x^7}

Therefore
x^{(7)/(4)=\sqrt[4]{x^7}\\eq RHS

But we have
x^{(7)/(4)=\sqrt[7]{x^4}

Therefore
LHS\\eq RHS

The corrected simplified expression
x^{(7)/(4)=\sqrt[4]{x^7}

Therefore Option D) is correct

Therefore the rational exponent expression which is not simplified correctly is


x^{(7)/(4)=\sqrt[7]{x^4}

User Alysha
by
5.8k points